Advances in microbial production of medium-chain dicarboxylic acids for nylon materials. Issue 2 (27th November 2019) - Li, Guohui; Huang, Dixuan; Sui, Xue; Li, Shiyun; Huang, Bing; Zhang, Xiaojuan; Wu, Hui; Deng, Yu
Abstract : Medium-chain dicarboxylic acids (MDCAs) are widely used in the production of nylon materials, and among which, succinic, glutaric, adipic, pimelic, suberic, azelaic and sebacic acids are particularly important for that purpose. Abstract : Medium-chain dicarboxylic acids (MDCAs) are widely used in the production of nylon materials such as nylon 5, 6 and nylon 6, 6, and among which, succinic, glutaric, adipic, pimelic, suberic, azelaic and sebacic acids are particularly important for that purpose, and also serve as platform chemicals for chemical, food, textile, pesticide, pharmaceutical and liquid crystal industries. Although most of these MDCAs are chemically synthesized, their biosynthesis has become more important due to the fast growth of biotechnology. Compared with chemical production and plant extraction, microbial-based production is more environmentally friendly and sustainable. In this review article, we critically comment existing methods for producing MDCAs and their biosynthesis, emphasizing metabolic engineering and synthetic biology strategies, which could help overcome barriers ahead and facilitate efficient bio-based production of MDCAs in the future.